2021
DOI: 10.1177/10690727211018977
|View full text |Cite
|
Sign up to set email alerts
|

Do Unnecessary Tasks Impair Performance Because They Harm Living a Calling? Testing a Mediation in a Three-Wave Study

Abstract: This three-wave study explored whether living a calling (at work) mediated the relation between unnecessary tasks (time wasting work tasks) and socio-contextual performance at work (cynicism, organizational citizenship behavior). Participants were 518 Finnish white- and blue-collar employees, who were followed up in 2018, 2019, and 2020. The results of structural equation modeling showed that unnecessary tasks at Time 1 related negatively to living a calling at Time 2, which, in turn, related to cynicism and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Calling, which refers to the attempt to connect one's work role with a broader sense of meaning and purpose at work and to hold other-oriented values as a vital source of motivation, employees with higher calling are more likely to perceive the significance and importance of their job, care less about low pay and poor working environments, and may even make self-sacrifices (Duffy et al, 2018(Duffy et al, , 2016. Previous research studies (Clinton et al, 2017;Mauno et al, 2022) have revealed that calling significantly influences job-related variables such as intrinsic motivation and career commitment. In this research, we expect the mediation effect of positive affect on the linkage between fit and organizational commitment will be moderated by calling.…”
Section: Ijchm 363mentioning
confidence: 99%
“…Calling, which refers to the attempt to connect one's work role with a broader sense of meaning and purpose at work and to hold other-oriented values as a vital source of motivation, employees with higher calling are more likely to perceive the significance and importance of their job, care less about low pay and poor working environments, and may even make self-sacrifices (Duffy et al, 2018(Duffy et al, , 2016. Previous research studies (Clinton et al, 2017;Mauno et al, 2022) have revealed that calling significantly influences job-related variables such as intrinsic motivation and career commitment. In this research, we expect the mediation effect of positive affect on the linkage between fit and organizational commitment will be moderated by calling.…”
Section: Ijchm 363mentioning
confidence: 99%
“…The hypothesis states that individuals develop the perception of having a calling for a work domain or set of activities through a cyclical process of exploration, involvement in the calling domain, and self-reflection. Empirical evidence supports this hypothesis (Dalla Rosa et al, 2019;Duffy et al, 2014;Mauno et al, 2022;Ahn et al, 2017;Sturges et al, 2019). The two approaches align and suggest that a calling develops through interaction with the environment and an understanding of the self.…”
Section: The Development Of a Callingmentioning
confidence: 82%
“…The hypothesis states that individuals develop the perception of having a calling for a domain or set of activities through a cyclical process of exploration, involvement in the calling domain and self-reflection. The a posteriori hypothesis found empirical support in Dalla Rosa et al (2019), Duffy et al (2014), andMauno et al (2022). Moreover, in-depth interviews conducted by Ahn et al (2017) revealed self-exploration and meaning-making from past experiences as the main mechanisms of a calling development.…”
Section: The Development Of a Callingmentioning
confidence: 84%
See 1 more Smart Citation
“…Significantly, illegitimate tasks have been identified as a severe problem across various workplaces, including the healthcare sector 6 , 15 , 30 , 31 , higher education 32 , IT professionals 33 , teachers 5 , engineers 17 , administrative staff 11 , blue-collar workers 34 , and also Red Cross volunteers 29 .…”
Section: Introductionmentioning
confidence: 99%